Effect of the German tonsillitis guideline on indication for tonsil surgery in patients with recurrent acute tonsillitis: a population-based study - Betz, Valerie; Boeger, Daniel; Buentzel, Jens; Hoffmann, Kerstin; Jecker, Peter; Kaftan, Holger; Mueller, Andreas; Radtke, Gerald; Geißler, Katharina; Guntinas-Lichius, Orlando (Scientific reports, 2023)
Evidence-based indication for tonsil surgery in patients with recurrent acute tonsillitis (RAT) is an ongoing matter of debate. Since introduction of the German tonsillitis guideline in 2015, the indication criteria for tonsil surgery have become much stricter. It is unclear, if this has changed the indication policy. A retrospective population-based study was performed including all 1398 patients with RAT admitted for tonsil surgery in all Thuringian hospitals in 2011, 2015, and 2019. Changes over the years concerning patients’ characteristics, number of tonsillitis episodes in the last 12 months treated with antibiotics (T12), and decision for tonsillectomy or tonsillotomy were analyzed using univariable and multivariable statistics. The surgical rates decreased from 28.56/100,000 population in 2011 to 23.57 in 2015, and to 11.60 in 2019. The relative amount of patients with ≥ 6 T12 increased from 14.1% in 2011 over 13.3% in 2015 to 35.9% in 2019. Most patients received a tonsillectomy (98% of all surgeries). Decision for tonsillotomy was seldom (1.2%). Multinomial logistic regression analysis with the year 2011 as reference showed that compared to the year 2015, the age of the patients undergoing surgery increased in 2015 (Odds ratio [OR] = 1.024; 95% confidence interval [CI] = 1.014–1.034; p < 0.001), and also in 2019 (OR 1.030: CI 1.017–1.043; p < 0.001). Compared to 2011, the number T12 was not higher in 2015, but in 2019 (OR 1.273; CI 1.185–1.367; p < 0.001). Stricter rules led to lower tonsil surgery rates but to a higher proportion of patients with ≥ 6 T12 before surgery. Tonsillectomy remained the dominating technique.